The organizational climate and its relationship with academic stress among students of the College of Physical Education and Sports Sciences at Thi Qar University - Hadi, Sara Amjad; Salman, Suhair Rahman (Journal of Neonatal Surgery, 2025)
The study aims to construct and design scales for organizational climate and academic stress among students of the College of Physical Education and Sports Sciences at the University of Thi-Qar. It seeks to identify the relationship between the scales of organizational climate and academic stress among these students, as well as to extract the standards and levels for both scales. The research population consisted of 849 students, divided into an exploratory sample of 12 students, a construction sample of 120 students, and an application sample of 80 students, resulting in a sample percentage of 24.97%. The researcher reached several conclusions, the most important of which were the construction of the organizational climate scale with 45 items belonging to three domains, and the construction of the academic stress scale with 45 items also belonging to three domains. The results showed varying frequencies and percentages, indicating high, very high, average, and low levels; however, the average level was predominant in the organizational climate scale, while a low level was predominant in the academic stress scale